Structure, syntax and "small-world" organization in the complex songs of California Thrashers (Toxostoma redivivum). Issue 1 (2nd January 2016) - Cody, Martin L.; Stabler, Edward; Sánchez Castellanos, Héctor Manuel; Taylor, Charles E.
Abstract: We describe songs of the California Thrasher ( Toxostoma redivivum), a territorial, monogamous species whose complex songs are composed of extended sequences of phonetically diverse phrases. We take a network approach, so that network nodes represent specific phrases, and links or transitions between nodes describe a subgroup structure that reveals the syntax of phrases within the songs. We found that individual birds have large and largely distinct repertoires, with limited phrase sharing between neighbours and repertoire similarity decaying between individuals with distance apart, decaying also over time within individuals. During song sequences, only a limited number of phrases (ca. 15–20) were found to be actually "in play" at any given time; these phrases can be grouped into themes within which transitions are much more common than among them, a feature contributing to a small-world structure. It appears that such "small-world themes" arise abruptly, while old themes are abandoned more gradually during extended song sequences; most individual thrashers switch among 3–4 themes over the course of several successive songs, and some small-world themes appear to have specific roles in starting or ending thrasher songs.